PENGARUH PANDEMI COVID-19 TERHADAP POLA KONSUMSI MAHASISWA DI KOTA TASIKMALAYA - Gian Riksa Wibawa; Depy Muhamad Pauzy (Universitas Serang Raya, 2022)
This study aims to see changes in student spending on consumption, transportation and the internet before and after the Covid-19 pandemic. This research is a quantitative, qualitative, and descriptive research with survey methods and literature studies. The questionnaire was submitted via Google Form with a total of 100 students as respondents distributed through various social media. The results of this study show that in the pre-pandemic period, students' needs for consumption ranked first with a percentage of 43%, followed by transportation needs at 38%, and the last order was the need for the internet. However, in the post-pandemic period there was a change, where the need for spending on the internet became the highest with a percentage of 59%, followed by consumption needs at 22% and lastly the need for transportation at 19%. This happens because students who migrate to study can return to their hometowns or parents' homes due to online lectures, so the need for consumption and transportation decreases, this is inversely proportional to the increasing need for the internet.